Evaluation of the Lithuanian Riﬂemen’s Union in the Public Space of the Klaipėda Region in 1923–1926 - Pocytė, Silva (History / Istorija, 2020)
Annotation. Te article analyses the issue of the Lithuanian Riﬂemen’s Union in the public space of the Klaipėda region in 1923–1926, based on the periodicals “Klaipėdos sargas” and “Klaipėdos garsas” published by the Riﬂemen’s Union in Klaipėda. Qualitative analysis of the content distinguishes three main problematic issues: the attitude of the riﬂemen towards the Lithuanianness of the country, Germanism and religion. Te Lithuanian Riﬂemen’s Union was one of the key support organisations that had to implement Lithuania’s integration policy in the Klaipėda region, therefore the analysis of the above aspects in the press allows revealing of the Riﬂemen’s Union’s reﬂections and perceptions in the Klaipėda region’s public space.